Study the Comparison of Gonadotropin Levels in Diabetes Mellitus Females. - Kadhim, Rawnaq J; Ahmed, Salman A (Al-Nahrain Journal of Science, 2018)
A cross sectional study was designed to assess the correlation of LH, FSH and HbA1c levels in patients with and without DM in premenopausal women, and the correlation of age with LH and FSH hormones in diabetic women, using the data that collected. It was conducted in the specialized centre for Endocrinology and Diabetes (SCED) in Baghdad city from December 2013 to September 2014. Hundred women with type II diabetes (30-49) and hundred healthy women in the same age and BMI as control during the luteal phase of menstrual cycle were enrolled. Patients assessed for HbA1C, FSH and LH levels. Results showed that HbA1c, LH and FSH were higher in diabetic premenopausal women compared with control individuals.